Draught requirement and physical properties in a Hapludalf at different management and traffic intensity levels - Rosa, David Peres da; Reichert, José Miguel; Mentges, Marcelo Ivan; Vieira, Davi Alexandre; da Rosa, Vanderleia Trevisan; Reinert, Dalvan José (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effect of traffic intensity and soil management on the draught demand of a fertilizer furrow‑opener, and on the physical properties of a Hapludalf. Treatments were: no‑tillage with natural traffic, no‑tillage with traffic intensity of 24.79 Mg km ha‑1, no‑tillage with traffic intensity of 49.59 Mg km ha‑1, minimum tillage and minimum tillage in compacted soil with 24.67 Mg km ha‑1. Data were collected for: total porosity; bulk density; penetration resistance; and for horizontal, vertical and draught forces demanded from the fertilizer planters. The subsoiling of minimum tillage used as an isolated technique did not reduce the compaction effects by a traffic intensity of 24,67 Mg km ha‑1. The traffic changes the soil structure but not the draught requirement. The changes in its intensity from 24.79 to 49.59 Mg km ha‑1 does not further affect in the evaluated properties.